Root morphology and seed and leaf ionomic traits in a Brassica napus L. diversity panel show wide phenotypic variation and are characteristic of crop habit - Thomas, C.L.; Alcock, T.D.; Graham, N.S.; Hayden, Rory; Matterson, S.; Wilson, L.; Young, S.D.; Dupuy, L.X.; White, Philip J.; Hammond, J.P.; Danku, J.M.C.; Salt, D.E.; et al. (Biomed Central, 2016)
Background